The tort responsibility of the health practitioner in the Saudi system - Al-Azzam, Saad Nasser; Muhammad, Ahmed Muhammad Ali Bashier (Journal of Economic, Administrative and Legal Sciences, 2022)
This research aims to study the importance of the medical profession and the work of the health practitioner towards the public and the individual, clarifying the meaning of medical errors and indicating their types and ways to prevent them, when the doctor bears responsibility for his error and what are the principles and criteria on which the jurists relied in determining the doctor’s responsibility for any harm that occurs to the patient as a result of his treatment. The research was built from a number of issues and issues that form a unity indicative of the topic I am going to research on, which is the health practitioner system and medical errors, and the researcher briefly talked about the five necessities and that the main goal that the Shariah of Islam brought is to preserve these necessities, which are: Preserving the religion Preserving the soul, preserving offspring, preserving money, preserving the mind, and any medical work must be based on achieving the interest in preserving these necessities. Including that the research talked about medication and the necessity of striving for it in order to achieve the interest of self-preservation, We find that the Saudi regulator mentioned in the system of practicing health professions as well as in its executive regulations and clarified the legal responsibility of the health practitioner and our comments on that from the research and from the practical reality and from here the researcher will shed light on the system of practicing health professions, as well as the criminal penalties resulting from the health practitioner’s breach of his duties towards The patient, and the researcher deals with the medical errors contained in the Saudi system, and the professional duties and responsibilities of the practitioner from the reality of the study of the Saudi system. Where this system was issued due to the noticeable emergence of medical errors, and to reduce these errors, a system must be approved and implemented.